2014
DOI: 10.1016/j.jfma.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin ameliorates neuropathic pain by suppressing HDAC1 expression in the spinal cord of spinal nerve ligation rats

Abstract: The present findings suggest that baicalin can ameliorate neuropathic pain by suppressing HDAC1 expression and preventing histone-H3 acetylation in the spinal cord dorsal horn of SNL rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 40 publications
0
75
0
1
Order By: Relevance
“…Systemic administration of HDAC inhibitor has also analgesic effect in formalin-evoked acute inflammation via expression changes of the metabotropic glutamate receptor (mGluR)2 in the dorsal root ganglion (DRG) and spinal cord (Chiechio et al, 2009). Peripheral nerve injury decreases histone acetylation and increases HDAC in the spinal cord (Cherng et al, 2014). Intrathecal administration of HDAC inhibitor has analgesic effect in peripheral nerve injury (Denk et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic administration of HDAC inhibitor has also analgesic effect in formalin-evoked acute inflammation via expression changes of the metabotropic glutamate receptor (mGluR)2 in the dorsal root ganglion (DRG) and spinal cord (Chiechio et al, 2009). Peripheral nerve injury decreases histone acetylation and increases HDAC in the spinal cord (Cherng et al, 2014). Intrathecal administration of HDAC inhibitor has analgesic effect in peripheral nerve injury (Denk et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between HATs and HDACs determine the net balance of histone acetylation (Binder et al, 2013). Mounting evidence suggests that during pain-related synaptic plasticity, the expression and activities of HDACs are dynamic (Geranton and Tochiki, 2015;Cherng et al, 2014;Matsushita et al, 2013;Kiguchi et al, 2013;Denk et al, 2013). Therefore, in the present review, we focus on mechanisms of histone acetylation and the role of HDACs in chronic pain and discuss recent attempts to treat chronic pain with HDAC inhibitors (HDACIs).…”
Section: Epigenetic Modulation: An Overviewmentioning
confidence: 99%
“…For example, it has been reported that in a rat model of spinal nerve ligation (SNL), HDAC1 expression in the nuclear fraction of the ipsilateral lumbar spinal dorsal horn was significantly increased, while acetyl-H3 was decreased from post-surgical day 1-7 (Cherng et al, 2014). However, in a spared nerve injury (SNI) model, the expression of HDAC1 was unchanged, whereas the expression levels of HDAC2 and 5 were decreased in the spinal dorsal horn 7 d after surgery (Shen et al, 2014).…”
Section: Dynamic Changes Of Hdac Expression and Histone Acetylation Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, two laboratories showed that class I HDAC, mainly HDAC1 , is important for neuropathic pain while Class II in important for inflammatory pain [147, 166167]. …”
Section: Introductionmentioning
confidence: 99%